Platelet-rich plasma combined with gypenosides for the treatment of psoriasis-like inflammation in mice - LI Dandan; WANG Bing; GE Yu; CHENG Hong; LI Mengxue; WANG Zhicheng; XIA Rong (Zhongguo shuxue zazhi)
[Objective] To investigate the therapeutic effect of platelet-rich plasma (PRP) subcutaneous injection combined with gypenosides (GPs) oral administration on BALB/c mouse psoriatic inflammation and explore its mechanism of action. [Methods] The 6-8 week-old female SPF BALB/c mice were randomly divided into five groups: control, model, PRP, GPs and PRP+GPs group, with 5 mice in each group. Imiquimod (IMQ) was used to induce psoriasis-like skin inflammation on the back of mice except the control group. The onset and severity of psoriasis-like inflammation in different treatment groups were evaluated by observing skin lesions, skin thickness and measuring PASI score. HE staining and Ki67 staining were used to evaluate the pathological changes and proliferation of keratinocytes in psoriasis-like skin lesions. Blood cell count, enzyme-linked immunosorbent assay and Western blot were used to explore the changes in circulating white blood cell count, cytokines IL-17A and TNF-α, and related signaling pathway proteins p-STAT3 and p-P38. [Results] At the end of the experiment (on day 6), scale scores of model, PRP, GPs and PRP+GPs group were 3.6±0.49, 1.8±0.75, 1.8±0.75, 1.2±0.40, respectively; the ratios of skin thickness (μm) were 0.86±0.18, 0.59±0.10, 0.56±0.07 and 0.42±0.09; PASI scores were 10.6±1.02, 4.0±0.63, 4.0±1.10 and 3.2±0.75. Compared with the model group, the number of scales (P<0.01), patch thickness (P<0.01) and PASI score decreased (P<0.0001) showed a certain therapeutic effect, and PRP+GPs group had the best effect. Pathological examination showed that both the epidermal layer thickness (P<0.01) and epidermal cell proliferation (P<0.05) decreased in all treatment groups; IL-17A expression levels were 9.02±2.54, 16.56±3.49, 10.01±1.83, 11.12±2.48 and 10.50±2.16, and TNF-α expression levels were 223.36±70.34, 377.36±58.47, 265.42±45.14, 262.94±33.29 and 268.94±26.80 respectively. The expression of skin tissue IL-17A (P<0.05) and TNF-α (P<0.05) decreased, along with the decreased expression of related signaling pathway proteins p-STAT3 and p-P38. [Conclusion] PRP combined with GPs can reduce the expression of IL-17A and TNF-α through the STAT3 and P38 signaling pathways, thereby alleviating inflammation and inhibiting the overproliferation of keratinocytes, thus improving psoriasis-like skin inflammation in BALB/c mice.